х = 500
Пошаговое объяснение:
10 · х - 2 000 = 3 000
10 · х = 3 000 + 2 000
10 · х = 5 000
х = 5 000 : 10
10 · 500 - 2 000 = 3 000
5 000 - 2 000 = 3 000
3 000 = 3 000
х = 500
Пошаговое объяснение:
10 · х - 2 000 = 3 000
10 · х = 3 000 + 2 000
10 · х = 5 000
х = 5 000 : 10
х = 500
10 · 500 - 2 000 = 3 000
5 000 - 2 000 = 3 000
3 000 = 3 000
Пошаговое объяснение:
10 · х - 2 000 = 3 000
10 · х = 3 000 + 2 000
10 · х = 5 000
х = 5 000 : 10
х = 500
10 · 500 - 2 000 = 3 000
5 000 - 2 000 = 3 000
3 000 = 3 000